Chondroprotective effect of curcumin and lecithin complex in human chondrocytes stimulated by IL-1β via an anti-inflammatory mechanism - Kim, Leeseon; Kim, Ji Yeon (Food science and biotechnology, 2019)
A complex of curcumin and lecithin developed to improve the solubility of curcumin, enhanced its chondroprotective effect via an anti-inflammatory mechanism. In macrophage, proinflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, prostaglandin E2 (PGE2), and nitric oxide (NO) were quantified. In addition, the activity of nuclear factor (NF)-κB was examined. With chondrocytes, inflammatory mediators were assessed by measuring the secretion levels of IL-6, IL-8, and PGE2, also the mRNA expression of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS). Metalloproteinases (MMPs), tissue inhibitor of metalloprotease (TIMP)-1, type II collagen (COL2), proteoglycan (PG), and hyaluronic acid (HA) were measured with respect to the articulation surface. The complex promoted the anti-inflammatory effect by the inhibition of inflammatory mediators. In addition, mRNA expression levels ameliorated. Furthermore, it was effective in decreasing extracellular secretion of polypeptides, also corresponding intracellular MMPs and TIMP-1. In conclusion, the complex may be developed as a functional supplement to maintain articulation health.